Bog bilberry phenolics, antioxidant capacity and nutrient profile. (15th June 2016) - Colak, Nesrin; Torun, Hülya; Gruz, Jiri; Strnad, Miroslav; Hermosín-Gutiérrez, Isidro; Hayirlioglu-Ayaz, Sema; Ayaz, Faik Ahmet
Highlights: Bog bilberry ( Vaccinium uliginosum L.) contains fructose and citric acid. Malvidin 3-glucoside is the main anthocyanin of bog bilberry. The anthocyanin fraction of the berry exhibited the highest antioxidant capacity. Phenolic acid in bog bilberry mainly occur as ester and glycoside forms. Bog bilberry is a source of antioxidants, phenolics and anthocyanins. Abstract: Phenolics and nutrient profiles of bog bilberry ( Vaccinium uliginosum L.) collected from high mountain pastures in northeast Anatolia (Turkey) were examined for the first time in this study. The major soluble sugar identified in the berry was fructose, following by glucose, and the main organic acid identified was citric acid, followed by malic acid. Eleven phenolic acids and 17 anthocyanin 3-glycosides were identified and quantified. Caffeic acid in the free and glycoside forms and syringic acid in the ester form were the major phenolic acids, and the major individual anthocyanin present in the berry was malvidin 3-glucoside (24%). The highest total phenolics and anthocyanin contents were obtained from the anthocyanin fraction in conjunction with the highest antioxidant capacity, followed by the polyphenolic and aqueous fractions, FRAP, ORAC and DPPH, in that order. Our findings can be used to compare bog bilberry with other Vaccinium berries and to help clarify the relative potential health benefits of different berries.